Supramolecular aspects of metal (M) dipicolinate anionic frameworks [M = Mn(II), Co(II), Ni(II), Cu(II) and Zn(II)] - Das, Babulal (My University, 2013)
Abstract not found
Baruah, Jubaraj Bikash
Keywords: CHEMISTRY